Pleistocene climate and geomorphology drive the evolution and phylogeographic pattern of Triplophysa robusta (Kessler, 1876) - Zhong, Hui; Sun, Yaxian; Wu, Huihui; Li, Shengnan; Shen, Zhongyuan; Yang, Conghui; Wen, Ming; Chen, Peng; Gu, Qianhong (Frontiers in Genetics, 2022)
Montane systems provide excellent opportunity to study the rapid radiation influenced by geological and climatic processes. We assessed the role of Pleistocene climatic oscillations and mountain building on the evolution history of Triplophysa robusta, a cold adapted species restricted to high elevations in China. We found seven differentiated sublineages of T. robusta, which were established during Mid Pleistocene 0.87-0.61 Mya. The species distribution model (SDM) showed an expansion of T. robusta during Last Glacial Maximum (LGM) and a considerable retraction during Last Interglacial (LIG). The deep divergence between Clade I distributed in Qinling Mountains and Clade II in Northeastern Qinghai-Tibetan Plateau (QTP) was mainly the result of vicariance event caused by the rapid uplifting of Qinling Mountains during Early Pleistocene. While the middle to high level of historical gene flow among different sublineages could be attributed to the dispersal events connected to the repetition of glacial period during Pleistocene. Our findings suggested that frequent range expansions and regressions due to Pleistocene glaciers likely have been crucial for driving the phylogeographic pattern of T. robusta. Finally, we urged a burning question in future conservation projection on the vulnerable cold adapted species endemic to high elevation, as they would negatively impacted by the recent rapid climate warming.